Estudo da interação do complexo antiNS1/NS1-DENV2 usando ancoramento molecular e métodos quânticos semi-empíricos - Silva, Leticia Alves da (2020)
Flaviviruses, such as Dengue and Zika, are diseases caused by viruses from the genus Fla- vivirus. Responsible for epidemic conditions, they have become a public health emergency of international concern. Tropical climate countries, such as Brazil, are prone to these epidemics because they have a favorable climate for the proliferation of the transmit- ting mosquito. The prophylaxis restricted to combating the transmitting agent and the lack of specific treatment have made studies focus on developing more accurate and early diagnoses, a promising alternative in changing the current scenario. In this sense, many re- searches have been studying the viral proteins encoded within the host cell. Among them, the non-structural protein 1 (NS1) has received focus due to its important role in repli- cation processes and viral evasion. Currently, the diagnosis of Dengue and Zika diseases is performed by using enzyme immunoassays, like ELISA, which uses immunoglobulin G as a marker. However, this kind of diagnosis is non-specific and may provide false- positive results due to cross-reactions. Alternatively, sNS1 protein is already used as a marker, and it provides early diagnostics without cross-reactions. However, the capability to discriminate between flaviviruses through the antigen-antibody complex affinity is still unknown. In this context, this study aims to understand the molecular interactions be- tween the non-structural protein of Dengue serotype 2 (NS1-DENV2) and a monoclonal antibody antiNS1. In order to evaluate the interacting affinity region through getting the antiNS1/NS1-DENV2 complex, we are proposing an in silico analysis protocol, which combines docking molecular and semiempirical approach. By using two molecular docking softwares (ClusPro and PatchDock), based on different global search algorithms, we got the initial configurations of the complex. Next, the Rosetta online server was used to re- fine those configurations. The bonding enthalpy (∆Hbind ) of the 22NS/DENV2 model and the 22NS/WNV crystallographic structure were calculated from their heat of formation, ∆H f . All ∆H f were calculated in MOPAC 2016 using the semiempirical Hamiltonian PM7, along with the MOZYME approach and implicit solvation model. The results showed that the 22NS/NS1-DENV2 complex interaction region is located on the Wing domain, in agreement with experimental epitopes mapping data. The value of ∆Hlig obtained from 22NS/DENV2 was -460.07 kJ mol−1 , which is comparable to ∆Hlig the crystallographic complex (-620.95 kJ mol−1 ). According to this, the proposed protocol might be a promising tool for discriminating accurate and imprecise models, providing models in agreement with experimental data. Therefore, this protocol is useful to evaluate the interaction region and the affinity for similar systems.